1968
DOI: 10.1042/bj1060123
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mitochondrial inhibitors on the respiration and energy-dependent uptake of iodide by thyroid slices

Abstract: The influence of mitochondrial inhibitors, including oligomycin, antimycin and rotenone, on the iodide and oxygen uptake and the nucleotide content of incubated sheep thyroid slices was investigated. Each inhibitor strongly suppressed both iodide and oxygen uptake, and decreased the nucleoside triphosphate content of the slices. In most cases the addition of glucose or mitochondrial substrates restored iodide uptake in inhibitor-treated slices. Inhibitor concentrations sufficient to inhibit iodide uptake stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1969
1969
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Although the biochemical steps involved in iodide trapping have not been elucidated, the process is energydependent (15). A role for a ouabain-sensitive Na+-K+-activated ATPase in this process has also been suggested (16), though a recent study did not find a stoichiometric relationship between these two processes (17).…”
Section: ±71 204+72mentioning
confidence: 97%
See 1 more Smart Citation
“…Although the biochemical steps involved in iodide trapping have not been elucidated, the process is energydependent (15). A role for a ouabain-sensitive Na+-K+-activated ATPase in this process has also been suggested (16), though a recent study did not find a stoichiometric relationship between these two processes (17).…”
Section: ±71 204+72mentioning
confidence: 97%
“…Iodide transport is energy-dependent (15), and the defect in the nodules could reflect an abnormality in production or coupling of energy for this process. An abnormality in energy production seems most unlikely since ATP concentrations in the nodules were not reduced (Table V).…”
Section: ±71 204+72mentioning
confidence: 99%
“…In studies of sheep thyroid slices, when respiration was inhibited and iodide transport blocked, addition of glucose partially restored iodide transport (27). In other studies, inhibition of glycolysis greatly inhibited colloid endocytosis, and glucose addition counteracted this effect (9).…”
mentioning
confidence: 98%
“…8). It has been suggested that glycolytic ATP may be the preferred source of energy for plasma membrane functions such as iodide transport and colloid endocytosis (4,9,27).…”
mentioning
confidence: 99%
“…iodide transport (Tyler et al 1968). However, ouabain does not directly interact with NIS and should not show a rapid effect on the iodide current in oocytes measured by voltage clamp.…”
Section: Resultsmentioning
confidence: 99%